Think How to Think: Studying the Relationship between Critical Thinking Skills and Academic Achievement of Learners at Higher Education (Journal of Social Sciences Review, 2023)
The purpose of this research was twofold; to identify the relationship between critical thinking skills and academic achievement of students and explore the teachers’ perceptions of students’ critical thinking skills in higher education. Both quantitative and qualitative methodologies were adopted to collect data from university students and teachers. A public sector university was involved through purposive sampling to collect data from teachers and students. A test was developed for students based on the literature on critical thinking skills. Academic achievement was measured through the CGPA of students. A total of 800 students appeared in the test. Simple linear regression was applied to map the relationship between students' critical thinking skills and academic achievement. To collect data from teachers, a semi-structured interview protocol was developed in line with the test content. In total, 20 teachers were involved in collecting data. Thematic analysis was carried out to analyze qualitative data. The results of linear regression showed that there was no relationship between critical thinking skills and the academic achievement of students. They mainly reported their teaching methods and strategies. They rated a moderate level of critical thinking skills of their students. These results were contrasted with available research in higher education.
Keywords: Critical Thinking Skills; Academic Achievement; Linear Regression; Thematic Analysis